2011
DOI: 10.1103/physrevlett.107.251301
|View full text |Cite
|
Sign up to set email alerts
|

Probing Loop Quantum Gravity with Evaporating Black Holes

Abstract: This letter aims at showing that the observation of evaporating black holes should allow the usual Hawking behavior to be distinguished from Loop Quantum Gravity (LQG) expectations. We present a full Monte Carlo simulation of the evaporation in LQG and statistical tests that discriminate between competing models. We conclude that contrarily to what was commonly thought, the discreteness of the area in LQG leads to characteristic features that qualify evaporating black holes as objects that could reveal quantum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Note that the black hole spectrum in the deep quantum regime (when n is small) has been studied numerically in [49,50] for instance.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the black hole spectrum in the deep quantum regime (when n is small) has been studied numerically in [49,50] for instance.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, we describe the black hole radiation process using statistical mechanical techniques together with some assumptions about the dynamical behavior of BHs close to equilibrium. In doing this we will basically follow the ideas of [27] leading to the computation of the integrated emission spectrum for a black hole (under some assumptions which will be made precise later). The simulated spectrography will allow for the study of deviations predicted by the old and new (holographic) models of LQG from the semiclassical Hawk-ing process expectation.…”
Section: Introductionmentioning
confidence: 99%
“…The idea proposed in [39] is to search for possible LQG signatures in the spectrum of evaporating black holes. The state counting for black holes in LQG relies on the isolated horizon framework (that is a boundary of the underlying manifold considered before quantization).…”
Section: Black Holesmentioning
confidence: 99%
“…However it was understood in [41,42] that the situation is different in LQG because the spacing of the energy levels decreases exponentially with the energy. In [39], this issue was readdressed and it was shown that several different signatures can in fact be expected.…”
Section: Black Holesmentioning
confidence: 99%